Medical Waste Management Practices in Nigeria, the Case of Lagos and Ibadan (2011)
Most developing countries are facing serious challenges on medical waste (MW) management. The current management practices of medical waste in Nigeria was studied using Lagos and Ibadan, an emerging mega city and the largest city in West Africa as case study. Sources of data were through questionnaire administration, waste sorting and characterization as well as sampling and analysis. The study revealed that there is no proper segregation of MW in most health care facilities studied. Over 75% of the MW handlers in Lagos and 98% in Ibadan are unaware of any policy and legislation regarding the management of MW. About 60% and 99%, respectively had no form of training in MW management and as such, are greatly exposed to different health risk. Furthermore, the States Waste Management Authority has no separate and appropriate dumpsites and landfills for disposal. The current system of MW management in Nigeria is in dire need of immediate attention and improvement. It is essential to develop a national policy on MW management and implementation of the existing ones to provide environmentally sound management measures to improve MW management in the country.